HUMAN CAPITAL IMPACT TOWARD IMPROVEMENT OF FOOD AND BEVERAGE SMALL MEDIUM ENTERPRISES IN MANADO - Mongi, Rifan E.; Tulung, Joy E.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Small medium enterprises has become a type of business that become a trend and increases year by year, in Indonesia SMEs have a stable position at the national level in economic development, its contribution to the Gross Domestic Product (GDP) of Indonesia reached 60.34% and employment at 97%. Central Bureau of Statistics (2018), the growth of SMEs in Manado is significant, which remains a concern of howâ€™s the SMEs improvement in Manado. This research aims to analyze the impact of human capital toward SMEs improvement in Manado. This research used qualitative method with depth interview to collect the data. The samples in this research are 15 owner of SMEs from food and beverages sector in Manado. The research finds that human capital have significant influence toward SMEs Improvement in Manado. Knowledge, Personal network, Experience, Innovation have positive result toward SMEs improvement, while Professional skill have no effect in SMEs improvement. From the result, it is recommended for the government to create more training, seminar for the entrepreneur, also those entrepreneur should pay more attention on what skill and where can they obtain it before start a SMEs.Â Keywords: SMEs, human capital, knowledge, personal network, experience, innovation, professional skill